2019
DOI: 10.3847/1538-4357/ab3f37
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference of High-density Nuclear Symmetry Energy from Radii of Canonical Neutron Stars

Abstract: The radius R 1.4 of neutron stars (NSs) with a mass of 1.4 M ⊙ has been extracted consistently in many recent studies in the literature. Using representative R 1.4 data, we infer high-density nuclear symmetry energy E sym (ρ) and the associated nucleon specific energy E 0 (ρ) in symmetric nuclear matter (SNM) within a Bayesian statistical approach using an explicitly isospin-dependent parametric Equation of State (EOS) for nucleonic matter. We found that: (1) The available astrophysical data can already improv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
90
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 116 publications
11
90
1
Order By: Relevance
“…Various studies have empirically identified correlations between various combinations of parameters that characterize the symmetry energy and its density dependence with the neutron star radius and tidal parameters [246,[266][267][268][269] or terrestrial experimental results [239,[270][271][272], as they all are linked to the low-density behavior of the equation of state around (twice) saturation. The tidal constraints from GW170817, and more recently radius constraints from NICER have been used to examine implications for the symmetry energy [273][274][275][276][277][278][279][280][281][282] as well as potential systematics in the mapping [283].…”
Section: Microscopic Propertiesmentioning
confidence: 99%
“…Various studies have empirically identified correlations between various combinations of parameters that characterize the symmetry energy and its density dependence with the neutron star radius and tidal parameters [246,[266][267][268][269] or terrestrial experimental results [239,[270][271][272], as they all are linked to the low-density behavior of the equation of state around (twice) saturation. The tidal constraints from GW170817, and more recently radius constraints from NICER have been used to examine implications for the symmetry energy [273][274][275][276][277][278][279][280][281][282] as well as potential systematics in the mapping [283].…”
Section: Microscopic Propertiesmentioning
confidence: 99%
“…As an example, shown in Figure 3 is the magnitude of symmetry energy at twice the saturation density of nuclear matter from nine recent analyses of neutron stars in comparison with the two results from earlier heavy-ion reaction experiments (from the FOPI-LAND [93] and the ASY-EOS [94] Collaborations by analyzing the relative flows and yields of light mirror nuclei, as well as neutrons and protons in heavy-ion collisions at beam energies of 400 MeV/nucleon). More specifically, the nine analyses were from (1) (Zhang and Li 2019) directly inverting observed NS radii, tidal deformability, and maximum mass in the high-density EOS space [95][96][97], (2) (Xie and Li 2019) a Bayesian inference from the radii of canonical NSs observed by using Chandra X-rays and gravitational waves from GW170817 [98] While certainly the model dependence and the error bars are still relatively large, all results from both heavy-ion reactions and neutron stars scatter around an overall mean of E sym (2ρ 0 ) ≈ 51 ± 13 MeV at a 68% confidence level, as indicated by the green line. The symmetry energy around 2ρ 0 is particularly interesting because the pressure around this density determines the radii of canonical NSs [5].…”
Section: Symmetry Energy At 2ρ 0 Extracted From Neutron Star Observablesmentioning
confidence: 99%
“…(Zhang et al 2018;Zhang & Li 2019a), one can examine how each NS observable may help constrain the high-density EOS parameter space. We note that results from the direct inversion and statistical inversion using the Bayesian approach were found consistent (Xie & Li 2019). As examples relevant for the present study, shown in Figure 4 are the constant surfaces of several observables and physics conditions in the 3D K sym −J sym −J 0 EOS parameter space: the NS maximum mass of M=2.14 M ⊙ (green surface) or 2.01 M ⊙ (pink surface), the radius of canonical NS R 1.4 = 12.83 km (yellow surface) or R 1.28 = 11.52 km (orange surface) for a NS of mass 1.28 M ⊙ , the dimensionless tidal deformability of canonical NS Λ 1.4 = 580 (red surface), and the causality surface (blue) on which the speed of sound equals the speed of light at the central density of the most massive NS supported by the nuclear pressure at each point with the specific EOS there (Zhang & Li 2019a).…”
Section: Observational Constraints On the High-density Eos Parameter mentioning
confidence: 56%
“…Indeed, observations of NSs using several different kinds of messengers in recent years have already provided some useful constraints on the high-density EOS. Within the model framework discussed above, we have recently studied how the three high-density EOS parameters are constrained by NS observations (Zhang et al 2018;Zhang & Li 2019a,b,c;Xie & Li 2019). These include the radii R 1.4 of canonical NSs, e.g., 10.62 < R 1.4 < 12.83 km from analyzing quiescent low-mass X-ray binaries (Lattimer & Steiner 2014), the dimensionless tidal deformability 70 ≤ Λ 1.4 ≤ 580 from the refined analysis of GW170817 data (Abbott et al 2018), and the latest NS maximum mass M = 2.14 +0.10 −0.09 M ⊙ from the observations of PSR J0740+6620 (Cromartie et al 2019).…”
Section: Observational Constraints On the High-density Eos Parameter mentioning
confidence: 99%